Optic Chiasmitis as an Isolated Manifestation of Myelin Oligodendrocyte Glycoprotein-Associated Disease – a Case Report - Nina Barankiewicz-Tyc; Karolina Kania; Wojciech Kozubski (Okulistyka)
Introduction The most common cause of chiasmopathy is compression of the optic chiasm by parasellar tumours. The tumours may produce any pattern of visual field defect depending on the tumour location and the patient’s chiasmal anatomy. Rare, non-compressive causes of chiasmopathy include, among others, infectious, post-infectious, inflammatory, autoimmune, demyelinating, toxic and ischaemic processes. Chiasmopathy can also occur due to trauma and radiation treatment.